"Acquired" subvalvular aortic stenosis after repair of several congenital cardiac defects - Tokel, Kürşad; Özme, Şencan; Çil, Ergün; Özkutlu, Süheyla; Çeliker, Alpay; Saraçlar, Muhsin; Bilgiç, Arman; Özer, Sema (The Turkish Journal of Pediatrics, 1996)
Discrete subvalvular aortic stenosis is a progressive lesion. In this report we presented nine patients who had no significant left ventricular-aortic obstruction at initial cardiac catheterization or echocardiographic examination, but later developed significant subvalvular aortic stenosis. Associated lesions included ventricular septal defect in three, patent ductus arteriosus in two, aortico pulmonary window in one, tetralogy of Fallot in one, supramitral membrane in one, and ventricular septal defect and patent ductus arteriosus in one case. Nine patients were diagnosed with subvalvular aortic stenosis 18 months to eight years after surgical correction. Eight of the patients required surgery for subvalvular obstruction. In conclusion, discrete subaortic stenosis is a rare, late complication of the surgical repair of several congenital heart defects. It is a progressive lesion after surgery; therefore these patients require careful follow-up.